Penerapan Permainan Tebak Kata Untuk Meningkatkan Keterampilan Berbicara Anak (Penelitian Tindakan Kelas di Kelompok B PAUD Lestari Bengkulu Tengah) - Marheni Budi Harti; Sumarsih Sumarsih; Anni Suprapti (Universitas Bengkulu, 2017)
The purpose of this research was to improve children's speaking skill through guessing words games at B group of PAUD Lestari in Bengkulu Tengah. Speaking skill consists of pronunciation aspect, enriching vocabulary, and sentence building. This research was a classroom action research (CAR) and conducted in 2 cycles, there’re 3 meetings for each cycle. The subject of the research was 12 children, there were 3 boys and 9 girls. The technique of collecting data was gathered by using observation. In analyzing the data, the researcher used average formula and learning completeness. The result of this research showed that there were an increasing number for speaking skill in pronunciation aspect, enriching vocabulary, and sentence building. In cycle I reach enough criteria. In cycle II increased with good criteria. Therefore, it is suggested for further researchers to improve children‘s speaking skill in sentence building aspect through guessing words or other various games.